Conjugated Copolymers of Vinylene Flanked Naphthalene Diimide - Fei,Z; Han,Y; Martin,J; Scholes,FH; Al-Hashimi,M; AlQaradawi,SY; Stingelin,N; Anthopoulos,TD; Heeney,M (Macromolecules, 2016)
We report the synthesis of a novel naphthalene diimide (NDI) monomer containing two (tributylstannyl)vinyl groups. The utility of this building block is demonstrated by its copolymerization with five different electron-rich comonomers under Stille conditions. The resulting high molecular weight polymers show red-shifted optical absorptions in comparison to the analogous polymers without the vinylene spacer and a significant increase in the intensity of the low-energy intramolecular charge transfer band. The polymers all exhibit ambipolar behavior in bottom-gate, top-contact organic thin-film transistors. The insertion of a solution-processed barium hydroxide layer between the polymer and the gold electrode led to unipolar behavior with improved electron mobilities.